Feedback as a strategy to change behaviour: the devil is in the details - Elaine Larson; Sameer Patel; David Evans; Lisa Saiman (2011)
Abstract Background Performance feedback is one of a number of strategies used to improve clinical practice among students and clinicians. Objectives The aims of this paper were to examine conceptual underpinnings and essential components for audit and feedback strategies, to assess the extent to which recently published audit and feedback interventions include these components and to recommend future directions for feedback to improve its educational and behavioural impact. Methods Based on the actionable feedback model, we examined the presence of four theoretical constructs – timeliness, individualization, lack of punitiveness and customizability – in studies published during 2009–2010 which included a feedback intervention. Results There was wide variation in the definition, implementation and outcomes of ‘feedback’ interventions, making it difficult to compare across studies. None of the studies we reviewed included all of the components of the actionable feedback model. Conclusions Feedback interventions reported to date, even when results are positive, often fail to include concepts of behaviour change. This may partially explain the large variation in approaches and in results of such interventions and presents major challenges for replicating any given intervention. If feedback processes are to be successfully used and disseminated and implemented widely, some standardization and certainly more clarity is needed in the specific action steps taken to apply behavioural theory to practice.